Formative and shared assessment in higher education. Clarifying concepts and proposing interventions from the formative and shared assessment network - Víctor Manuel López Pastor (Psychology, Society & Education, 2012)
The purpose of this paper is threefold: (a)-making an introduction to the formative and shared assessment at Higher Education teaching and tracing its connections within the process of convergence towards the Higher Education European Area (HEEA), (b) - establishing a conceptual clarification of the different terms that are currently used in the literature in relation to the formative assessment and student participation in assessment, (c)- making a brief introduction to the proposal of Formative and Shared Assessment in Higher Education that we have developed from our Network. The monograph included in this issue is based on the Formative and Shared Assessment Network in Higher Education, and it shows the evolution and the different lines of innovation and research that participants have been developed for six years. In the first section of this paper an introduction of the Formative and Shared Assessment in Higher Education and its connection with the process of Convergence towards the HEEA is showed. In the second section we carry out a conceptual and terminological clarification on the Formative and Shared Assessment in Higher Education, suggesting some solutions for the terminological confusion on this issue that has arisen in recent years. In the third section we analyze the state of the formative and shared assessment in Higher Education and the evidence found so far on its advantages regarding traditional models. In the fourth and final section we show a concrete proposal of formative and shared assessment in higher education that has been proved within our Network and which could be applied to other contexts.